A comprehensive, multi-center, immunogenomic analysis of melanoma brain metastases - Lucy Boyce Kennedy; Amanda E. D. Van Swearingen; Marissa R. Lee; Layne W. Rogers; Alexander B. Sibley; Jeff Sheng; Dadong Zhang; Xiaodi Qin; Eric S. Lipp; Swaminathan Kumar; Aron Joon; Pixu Shi; et al. (Acta Neuropathologica Communications)
Abstract Background Melanoma brain metastases (MBM) have a unique molecular profile compared to extracranial metastases (ECM). Description of the biological features and clinical outcomes of MBM will facilitate the design of rational therapies. Methods We examined the mutational landscape and gene expression profiles of MBM (74 patients) and ECM (34 patients) in paired patient samples from a previously published dataset with whole-exome sequencing (WES) and RNA sequencing (RNAseq) data from MD Anderson Cancer Center (MDACC). We also present findings from MBM from a new cohort of 14 patients from Duke University to strengthen investigation of somatic mutations and gene expression profiles. Gene Set Enrichment Analysis (GSEA) was used to compare paired MBM versus lymph node (LN) metastases and skin metastases. Relative immune cell abundance was inferred using deconvolution methods. Survival outcomes from craniotomy and associations with biological features, BRAF mutation status, and PTEN expression were assessed. Results GSEA found that autophagy signaling pathways are enriched in MBM versus LN and skin metastases. BRAF was the most frequently mutated clinically relevant gene in MBM and ECM, with NRAS and PTEN also frequently altered in MBM. The most strongly upregulated genes in autophagy pathways were glial fibrillary acidic protein (GFAP) and hemoglobin beta (HBB). An increased proportion of immune-suppressive M2 compared to tumor-suppressive M1 macrophages in MBM and ECM was identified. There was not sufficient evidence for an association between BRAF V600 mutation status or expression and overall survival (OS) from craniotomy. Conclusions The mutational landscape and gene expression of MBM from the Duke cohort resembled those previously reported in the MDACC cohort. Upregulation of autophagy pathways was observed in patient-matched MBM versus LN and skin metastases due to upregulation of two genes, GFAP and HBB. In MBM, higher M2:M1 ratio may contribute to a therapeutically relevant immune-suppressive tumor microenvironment (TME).